Dewan Perwakilan Daerah Republik Indonesia dalam Perspektif Teori Bicameralisme - Dody Nur Andriyan (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2018)
After the amended of Indonesian Constitution1945, there is controversy about the position and function of the DPD as representative institution. This article examines the theoretical concepts and applications of bicameralism and unicameralism in many countries in the world and contextualizes them in Indonesia. There are five concepts of ius constituendum that can be explored in this article; First the DPD has the authority of legislation, supervision, and valuation; Second, the DPD has the authority to discuss and participate in deciding all the draft bills proposed by the DPR; Third, the DPD has initiative right to submit a draft bill, but is limited to certain regional affairs; Fourth, the structure and position of the MPR were substituted as a joint house for the DPR and DPD. Fifth, the MPR does not need its own General Secretariat. The MPR also does not require permanent leadership, because it can be held alternately by the leaders of the DPR and DPD.